Locoregional recurrence after nephrectomy for localized renal cell carcinoma: Feasibility and outcomes of different treatment modalities. (4th May 2022) - Liu, Yang; Zhang, Xinyue; Ma, Huali; Tian, Li; Mai, Lixin; Long, Wen; Zhang, Zhiling; Han, Hui; Zhou, Fangjian; Dong, Pei; He, Liru
Abstract: Background: Locoregional recurrence after nephrectomy for localized renal cell carcinoma (RCC) is rare with diverse manifestations. The selection criteria and efficacy of different treatments are unanswered. The objective was to compare different treatment modalities and present data on stereotactic body radiotherapy (SBRT) for recurrent RCC. Materials and Methods: Patients with locoregional recurrence after nephrectomy without distant metastasis were identified from institutional big data intelligence platform between 2001 and 2020. Patients receiving local therapy (surgery or SBRT) or systemic therapy alone (targeted therapy or PD‐1 inhibitors) were divided into two groups. Progression‐free survival (PFS) and overall survival (OS) were analyzed using Kaplan–Meier method, Cox regression model. Patients were matched with propensity score matching. Results: Among 106 patients, 33 (31.1%) received systemic therapy alone and 73 (68.9%) received local therapy. Local therapy was surgery in 34 patients (32.1%) and SBRT in 39 (36.8%) patients. Patients treated with systemic therapy alone had more non‐clear cell type ( p  = 0.044), more advanced T stage ( p  = 0.006), higher number ( p  = 0.043) but smaller size of lesions ( p  = 0.042). Patients receiving local therapy had significantly longer PFS than systemic therapy (19.7 vs. 7.5 months, p  = 0.001). After matching, the PFS in the local therapy group remained higher (23.9 vs. 7.5 months, p  = 0.001). The 2‐year OS of the local therapy group and systemic therapy group was 91.6% and 71.8%, respectively ( p  = 0.084). Local therapy was associated with better PFS (HR 0.37; p  = 0.0003) and OS (HR 0.23; p  = 0.002) in multivariate analysis. Grade 2 or higher toxicities related to local therapy occurred in nine patients. Conclusions: Local therapy could delay disease progression compared with systemic therapy alone. SBRT is safe and effective for locally recurrent RCC. Abstract : Treatment options for local recurrence of renal cell carcinoma (RCC) following nephrectomy are expanding. Our study compares different treatment modalities and elucidates that local therapy could delay disease progression compared with systemic therapy alone. SBRT is safe and effective for locally recurrent RCC.